Surfactin induces maturation of dendritic cells in vitro. Issue 5 (6th October 2016) - Xu, Wenwen; Liu, Haofei; Wang, Xiaoqing; Yang, Qian
Abstract : This was the first report of which we were aware concerning the effects of surfactin on DCs maturation and NF-κB signalling pathway might be involved in this process. Abstract : Surfactin has multiple immune activities, such as triggering immune-related defense responses and enhancing humoral and cellular immune responses. Although, the mechanisms are still unclear. The maturation of dendritic cells (DCs) is essential for inducing downstream immune response. To shed light on the mechanisms of surfactin-induced immune activities, we verified the influences of surfactin on DCs maturation. The results showed that after stimulated with 20 μg/ml surfactin for 24 h, DCs were conferred morphologic and phenotypic characteristics of a mature state, showing an increased shape index and up-regulated expressions of major histocompatibility complex II (MHCII) and CD40. Moreover, surfactin also induced DCs to release IL-6 and tumour necrosis factor-α (TNF-α), indicating that DCs were functionally mature. In addition, the IκB-α level in surfactin-treated DCs was significantly reduced whereas the nuclear p65 level was notably increased, preliminarily indicating that nuclear factor-kappa B (NF-κB) signalling pathway might play an important role in surfactin-induced DCs maturation.